Analysis of Customer Loyalty in Digital Video Streaming Applications Through Satisfaction and Trust Factors in Greater Jakarta - Yogie Ajie Pratama, Devi Puri, Aditya Putri Pertiwi, Sfenrianto, Jarot S. Suroso (International Journal of Advanced Science and Technology, 2020)
Digital streaming applications have to experience rapid expansion, proven by the current digital industry are competing on creating Video on Demand service. Viewers of Video on Demand are recorded surpassing yearly viewers of cinema or movie theater. Based on a brief survey that has been done indicates digital video streaming applications users have used more than one video streaming. It shows that customers in Indonesia have a behavior of quick brand displacement. Therefore, the question in this research is what factors that can influence customer loyalty rank on using digital video streaming applications in Greater Jakarta? Also knowing the significant impact that can influence customer loyalty in Greater Jakarta. Keywords: Digital streaming, Trust, Satisfaction, Customer Loyalty